Simulation Studies for JIT Production - CHU, Chao-Hsien (Institutional Knowledge at Singapore Management University, 1992)
The success of Japanese industry and manufacturing has been attributed to several factors, including government co-operation with and support for industry, the Japanese management style, and the cultural and social structure of Japanese society. Recently, much attention has been focused on Japanese production management techniques, especially on the design and implementation of just-in-time (JIT) systems with kanban. Several methodologies have been used in studying JIT production, among which computer simulation has received the most attention. Yet, little effort has been put into synthesizing the related literature, nor has the researcher examined the status quo. The purpose of this paper is to examine how extensively and sufficiently simulation has been used in studying JIT production. As can be seen from the study, many simulation-related statistical issues were ignored or neglected in previous studies. This ignorance may leave simulation results suspicious and hard to explain.